Biomarkers of drug-induced liver injury - Atallah, Edmond (2024)
Idiosyncratic drug-induced liver injury (DILI) is an unpredictable clinical event with no available biomarkers; specific phenotypes of DILI have been associated with certain drugs. The research presented in this doctoral thesis sought to evaluate the characteristics of diagnostic and prognostic non-genetic DILI biomarkers and set a direction for future studies to allow the clinical application of biomarkers in practice. First, a systematic review of DILI biomarkers that included 14 studies found that there is a clear need for research in this area and highlighted the necessary steps such as the inclusion of non-DILI control groups, needed to develop and validate diagnostic biomarkers and prognostic models. Two specific types of DILI were also investigated: chronic DILI due to methotrexate (MTX) and acute DILI due to checkpoint inhibitors (CPI).